Seasonal Variation in Chemical Composition of Total Suspended Particles During the COVID-19 Pandemic in the Source Area of Urumqi River, Tianshan, China - Zheng, Cunying; Li, Zhongqin; Zhang, Xin; Jiang, Huimin; Zhou, Xi (Frontiers in Earth Science, 2022)
The research of atmospheric aerosol in mountain glacier areas has attracted more and more people’s attention. For the first time, a field observation study of total suspended particles (TSPs) for four seasons from September 2019 to August 2020 was carried out at the Tianshan Glaciological Station in the source area of Urumqi River, East Tianshan Mountains, China. The TSPs presented typical seasonal characteristics of high in autumn and low in winter, with the annual average value of 181 ± 170 μg m−3. Concentrations of Ca2+, SO42−, NO3−, Cl−, NH4+ and K+, OC, EC were elevated in autumn. The influence of stationary source emissions was stronger than mobile sources, which was explained by the average ratio of NO3−/SO42− (0.31 ± 0.17). The concentration of secondary organic carbon (SOC) was higher in summer and autumn, especially in summer, indicating that secondary formation processes of organic aerosols were frequent in summer. Impact of fossil fuel combustion sources were evident over the Glaciers, corroborated by the diagnostic mass ratios of OC/EC (0–21.4, 3.38) and K+/EC (0–0.31, 0.08). The factor analysis illustrated that aerosols were mainly affected by rock salt, dust, coal combustion, and automobile exhaust. The local sources made significant contributions to TSPs in the source of Urumqi River by the results of Results of Hybrid Single Particle Lagrangian Integrated Trajectory (HYSPLIT) model and potential source contribution function (PSCF).